2021
DOI: 10.3390/nano11071826
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Dependence of Nanoparticles Magnetothermal Properties on Their Size for Hyperthermia Applications: A Case Study for La-Sr Manganites

Abstract: Magnetic oxides are promising materials for alternative health diagnoses and treatments. The aim of this work is to understand the dependence of the heating power with the nanoparticle (NP) mean size, for the manganite composition La0.75Sr0.25MnO3 (LSMO)—the one with maximum critical temperature for the whole La/Sr ratio of the series. We have prepared four different samples, each one annealed at different temperatures, in order to produce different mean NP sizes, ranging from 26 nm up to 106 nm. Magnetization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…The theoretical estimation of the SAR parameter has shown that this value increases with the incorporation of nanoparticles into the polymer shell (sample 0c1s). The capsules 0c1s are capable of heating by 10–15 °C based on the experimental results, which are presented in previous studies. A slow heating rate to a temperature of 42 °C using an external alternating magnetic field is relevant for hyperthermia. The release of a drug from capsules with MNPs embedded in the shell can be achieved by hyperthermia.…”
Section: Resultsmentioning
confidence: 96%
“…The theoretical estimation of the SAR parameter has shown that this value increases with the incorporation of nanoparticles into the polymer shell (sample 0c1s). The capsules 0c1s are capable of heating by 10–15 °C based on the experimental results, which are presented in previous studies. A slow heating rate to a temperature of 42 °C using an external alternating magnetic field is relevant for hyperthermia. The release of a drug from capsules with MNPs embedded in the shell can be achieved by hyperthermia.…”
Section: Resultsmentioning
confidence: 96%
“…Currently, nanoparticles belong to highly advanced and specialized biomedical products [ 1 ]. There are several interesting applications of nanoparticles in medicine and pharmacy: for example, in medical imaging, as nanocomposites, filters, components of drug delivery systems, and formulations for the treatment of cancer [ 2 , 3 , 4 , 5 ]. Gold nanoparticles have found applications in analytical procedures for the detection of cancer cells, proteins, and antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…For relaxation loss to be the major loss mechanism and hysteresis loss to be ignored, the particles should exhibit superparamagnetic behavior. In such a state, the ambient temperature T should be above the blocking temperature TB of the particles [70]. It is worth noting that the values of coercivity for all samples are relatively low, as shown in Table 2.…”
Section: Assessment Of Sarmentioning
confidence: 93%
“…Another study on 35 nm manganese ferrite nanoparticles of concentration 3 mg/mL at a field intensity of 350 G and a frequency of 765.95 kHz showed that the particles gave an SAR value of 70 W/g [74], while Muhammad Nauman et al studied gadolinium silicide nanoparticles and calculated an SAR value of 3.7 W/g for 43 nm particles at a field of 171 Oe and a frequency of 327 kHz [75]. Finally, a recent study using nanoparticles of different diameters based on La-Sr manganites, and with a low Curie temperature, gave SAR values ranging from 5.6 to 30 W/g [70].…”
Section: Assessment Of Sarmentioning
confidence: 99%